Gastrointestinal parasites in Chinstrap Penguins from Deception Island, South Shetlands, Antarctica - Vidal, V.; Ortiz, J.; Diaz, Julia Inés; Ruiz de Ybañez, M. R.; Amat, M. T.; Palacios, M. J.; Benzal, J.; Valera, F.; de la Cruz, C.; Motas, M.; Barbosa, A. (Parasitology Research)
Knowledge about parasites of Antarctic birds is fragmented and scarce. The aim of this work is to contribute to the knowledge of gastrointestinal parasites of the Chinstrap Penguin (Pygoscelis antarctica) from Deception Island (South Shetlands, Antarctica). Gastrointestinal tracts of 64 fresh dead individuals (61 chicks and three adults) were collected from December 2006 to February 2009 and examined for macroparasites. Three adult parasite species were found: two Cestoda species (Parorchites zederi and Tetrabothrius pauliani) and one Nematoda species (Stegophorus macronectes). Also, immature acanthocephalans (Corynosoma sp.) were found in one penguin. The low parasite richness observed could be related to the stenophagic and pelagic diet of the host species. False negatives were found in coprological studies. Fil: Vidal, V. . Universidad de Murcia; España. Consejo Superior de Investigaciones Cientificas; España Fil: Ortiz, J. Universidad de Murcia; España. Consejo Superior de Investigaciones Cientificas; España Fil: Diaz, Julia Inés. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico La Plata. Centro de Estudios Parasitológicos y de Vectores (i); Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina Fil: Ruiz de Ybañez, M. R. Universidad de Murcia; España. Consejo Superior de Investigaciones Cientificas; España Fil: Amat, M. T. Consejo Superior de Investigaciones Cientificas. Estacion Experimental de Zonas Aridas; España Fil: Palacios, M. J. Consejo Superior de Investigaciones Cientificas. Estacion Experimental de Zonas Aridas; España Fil: Benzal, J. Consejo Superior de Investigaciones Cientificas. Estacion Experimental de Zonas Aridas; España Fil: Valera, F. Consejo Superior de Investigaciones Cientificas. Estacion Experimental de Zonas Aridas; España Fil: de la Cruz, C. Universidad de Extremadura; España Fil: Motas, M. Universidad de Murcia; España Fil: Barbosa, A. Consejo Superior de Investigaciones ...